Ethno‐political socialization of young children in societies involved in intractable conflict: The case of Israel. (26th November 2021) - Nasie, Meytal; Reifen Tagar, Michal; Bar‐Tal, Daniel
Abstract: This paper presents an analysis of the ethno‐political socialization of young children in the context of intractable conflict, drawing on the case of Israeli society. The analysis is based on the integrative developmental‐contextual theory (IDCT), which proposes that in the context of intractable conflict, from a very early age onward, in‐group members acquire a socio‐psychological repertoire that consists of narratives, beliefs, attitudes, and emotions related to the conflict and to the rival group. IDCT highlights three central components that dictate the nature of this socio‐psychological repertoire: children's normative developmental trajectory, the context in which the development takes place, and the ethno‐political socialization that is performed by societal agents. We discuss the interaction between these components in socializing children's socio‐psychological repertoire, and ways to change the course of socialization in the context of intractable conflict towards peace‐oriented socialization.